S/TEM examination and nanomechanical response of W-Eurofer joints brazed with Cu interlayers - Izaguirre, I.; Roldán, Marcelo; de Prado, J.; Bonache, V.; Sánchez, M.; Ureña, A. (My University, 2022)
In this article, a preliminary microscale study of a brazed joint of two materials that will conform the future fusion reactors is carried out. Tungsten will act as plasma-facing material attached to a structure made of some reduced activation ferritic-martensitic steel (Eurofer-like steel). The proposed brazing process introduces copper as filler material and develops the thermal process in a high vacuum atmosphere at 1135¿°C for 10¿min. The resultant microstructure is characterised by forming a diffusion layer in contact with tungsten base material constituted by W, Fe and Cr. In addition, an iron-rich phase is formed between the diffusion layer and Cu braze region. This steel band presented two different structures: a typical martensite lath structure and another without it. At the centre of the steel band, the laths are replaced by a more homogeneous matrix where copper precipitates nucleated due to its enrichment in this element during the brazing process. It is worth highlighting the presence of dislocations and residual stresses in all the different phases that appear associated with the brazing process. This presence of dislocation stresses shows how the nanomechanical analysis increases the modulus and hardness values of the steel band concerning the Eurofer base material. The diffusion layer presents the highest values in the mechanical characterisation due to its morphology and the components that constite the phase.